Teaching practice and evaluation: strategy for continuous improvement in high quality accreditation processes (2019)
The objective of this research was to analyze the evaluation of the teaching performance of the Professional Technician Program in Police Service (TPSP), redesigning the evaluation instruments and the protocol of the pedagogical assessment system, using a quantitative approach of descriptive type, carrying out an analysis univariate, using 2 by 2 contingency tables. Thus the level of agreement between evaluators was determined, correlating the 8 behavioral variables of the teacher evaluation: pedagogical planning, teaching and learning strategies, methodological development, learning evaluation, implementation of academic credits, living spaces, and knowledge domain and communication skills. An evaluation was carried out on 14 educational sites and the results of peer visits by the National Accreditation Council (CNA), using a validated questionnaire, along with the self-evaluation, hetero-evaluation and co-evaluation of 32 TPSP teachers and 296 Students. It was concluded that communicative skills and teaching-learning strategies are the variables that most affect the teacher evaluation by students, with an almost perfect level of agreement between evaluators (Cohen's Kappa of 0.9).